Pembentukan Kevikepan Berbasis Karesidenan: Sejarah Strategi Pastoral Teritorial Keuskupan Surabaya - Laksito, Petrus Canisius Edi (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
With its vast scope, the Diocese of Surabaya is divided into 46 parishes grouped in 8 vicariates. In recent pastoral situations, strengthening the vicariate is a priority, but conceptually there has never been any adequate study on this topic. To make an adequate study, this work covers the history of the former residencies of Surabaya, Kediri, Madiun, dan Rembang because in reality the Diocese of Surabaya would later use this colonial administrative basis of the regional government as the basis for dividing its territory into vicariates. Having that rationale, this paper then discusses the formation history of the Diocese of Surabaya and the formation of the vicariates in the territory of the Diocese based on the ex-residencies’ territorial administration. After making an analysis on the divisions of the Diocese into vicariates since 1983 this paper ends with a conclusion.